The Law of Natural Resources Management for Economic Prosperity: A Critical Analysis of Law No. 3 of 2020 on Mineral and Coal Mining - Wondal, Nancy Syavois Allen; Hasibuan, Fauzie Yusuf; Rungsimanop, Phattarawadee (International Journal of Contemporary Sciences (IJCS), 2024)
This research critically analyzes Law No. 3 of 2020 on Mineral and Coal Mining, focusing on its impact on natural resource management for economic welfare in Indonesia. Utilizing a normative legal research method, the study examines the law’s potential to strengthen the mining sector and increase its contribution to the national economy. While the law aims to boost investment and revenue, it faces significant challenges related to environmental sustainability, local community rights, and governance. The findings reveal that criticisms of Law No. 3/2020 underscore the need for a more balanced approach, ensuring that economic interests do not compromise environmental protection and social justice. To achieve sustainable, fair, and transparent mining sector management, governance reforms and stronger law enforcement are essential. This will ensure that Indonesia's natural resources are managed equitably for the benefit of all, not just a select few.